The Effect of Current Ratio, Debt to Equity Ratio, Total Asset Turnover and Firm Size on Profit Growth in Food and Beverages Companies - Mega Ayu Wulandari; Sri Sudarsi (UNIVED Press, 2024)
The purpose of this study was to analyze the effect of the current ratio, debt to equity ratio, total asset turnover and firm size on profit growth in food and beverages companies on the Indonesia Stock Exchange from 2018 to 2022. The research sample used was purposive sampling. This study uses secondary data in the form of annual financial reports of food and beverage companies listed on the Indonesia Stock Exchange. The data in this study will be tested with several stages of testing, namely the descriptive statistical test, the classic assumption test which consists of testing all hypotheses through the coefficient of determination test, partial test (t test) and simultaneous test (f test). The results of this study indicate that the current ratio has a negative and insignificant effect on the profit growth of food and beverages companies, the debt to equity ratio has a negative and not significant effect on the profit growth of food and beverages companies, Total Asset Turnover has a positive and significant effect on the profit growth of food and beverages companies. beverages, firm size has a negative and insignificant effect on the profit growth of food and beverages companies.